Comments On The Cryptanalysis Of An Identity-Based Strong Designated Verifier Signature Scheme - Rasslan, Mohamed; Nasreldin, Mahmoud M. (Procedia computer science, 2022)
In this paper, we explain that the proposed modification to an identity-based strong designated verifier signature scheme (Lecture Notes in Electrical Engineering, vol. 164, no. 1, Springer-Verlag, 2012) is not secure. This scheme has a short signature size, low communication cost, and low computational cost. But, it does not satisfy the required authentication property in a designated verifier signature scheme. In particular, we introduce an attack that enables anybody to verify the signature.